Herança deixada pela ditadura militar no ensino da educação física escolar - Treft, Thaís Stéphanie [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This work has addressed what was the legacy left by the military dictatorship in the teaching of physical education at school, taking into account the historiography of Physical Education, sport, and all participation and government interference in the period of military dictatorship between 1964-1985. As a basic principle of this analysis, we considered the development of physical education in the period, therefore, preliminary studies show how the pedagogical practice arising from the militarisation became a reference almost exclusively for the bodily activities, within or outside the school. The main objective was to see which methods and visions inherited from the military government are still part in the teaching of physical education at school, therefore, to make this analysis was also responded, in parts, which remnants still influence the sport at school. The method used was an analysis based on a review of the literature, with studies of authors who have visions and theories about why and what was the intention of the military rulers Implement these techniques and methods

Este trabalho abordou qual foi a herança deixada pela ditadura militar no ensino da Educação Física Escolar, levando em conta a historiografia da Educação Física, o esporte, e toda participação e interferência governamental no período da ditadura militar entre 1964-1985. Como princípio básico dessa análise, foi considerado o desenvolvimento da Educação Física no período, pois, estudos preliminares mostram como a prática pedagógica advinda da militarização tornava-se referência praticamente exclusiva para a prática de atividades corporais, dentro ou fora da escola. O objetivo principal foi constatar quais métodos e visões herdadas do governo militar ainda fazem parte no ensino da Educação Física Escolar. Consequentemente, ao fazer essa análise, também foi respondido, em partes, quais resquícios ainda influenciam o esporte na escola. O método utilizado foi uma análise pautada em uma revisão bibliográfica, com estudos de autores que apresentam visões e teses sobre o porquê e qual era a intenção dos governantes militares implementarem tais técnicas e métodos
Keywords: Educação fisica; Ditadura; Educação física - Estudo e ensino; Historiografia; Esportes; Brasil - Historia - 1964-1985